2010
DOI: 10.1109/tnet.2009.2022369
|View full text |Cite
|
Sign up to set email alerts
|

Weighted Spectral Distribution for Internet Topology Analysis: Theory and Applications

Abstract: Abstract-Comparing graphs to determine the level of underlying structural similarity between them is a widely encountered problem in computer science. It is particularly relevant to the study of Internet topologies, such as the generation of synthetic topologies to represent the Internet's AS topology. We derive a new metric that enables exactly such a structural comparison, the weighted spectral distribution. We then apply this metric to three aspects of the study of the Internet's AS topology. (i) we use it … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
65
0
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(69 citation statements)
references
References 31 publications
(56 reference statements)
1
65
0
3
Order By: Relevance
“…The greater number of peering links between ASes at IXPs lead to those ASes getting deeper into the core of the Internet with decreasing emphasis on connections with upper tier ASes. The authors in [36,37] have all pointed towards this evolution characteristic of the Internet and our coreness metric based result presents a theoretical confirmation of these observations. Node and edge betweenness are two measures of centrality from which further inferences can be made about the effects of IXPs peering links.…”
Section: Analysis and Discussionsupporting
confidence: 83%
“…The greater number of peering links between ASes at IXPs lead to those ASes getting deeper into the core of the Internet with decreasing emphasis on connections with upper tier ASes. The authors in [36,37] have all pointed towards this evolution characteristic of the Internet and our coreness metric based result presents a theoretical confirmation of these observations. Node and edge betweenness are two measures of centrality from which further inferences can be made about the effects of IXPs peering links.…”
Section: Analysis and Discussionsupporting
confidence: 83%
“…The normalised Laplacian spectrum of ASlevel topologies has been shown to differ significantly from that of synthetically generated topologies [21]. Recently, a weighted spectral distribution metric has been proposed and shown that synthetically generated graphs can be fine-tuned using spectral properties [22]. While previous studies utilised graph spectra to analyse logical level topologies, in this study we focus on physical networks and how they relate to each other structurally.…”
Section: Background and Related Workmentioning
confidence: 99%
“…Additionally, bipartite graphs are very relevant in the Internet, as such subgraphs correspond to nodes that have identical sets of neighbors. Studying those nodes would be of particular interest to understand the structure of the Internet as these are duplicated structures in the graph [8]. Let Third, we index the triangle structure which is a clique structure of three nodes as shown in Figure 1-(f).…”
Section: Structure 2: Complete Bipartite (K Mn )mentioning
confidence: 99%